2019
DOI: 10.1002/jmv.25584
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological evidence of hepatitis B virus infection in the development of gastric adenocarcinoma

Abstract: Gastric cancer (GC) is one of the infection-related cancers. Helicobacter pylori and Epstein-Barr virus (EBV) were established risk factors for GC. Recently, there are several reports showing the inconsistent association between hepatitis B virus (HBV) infection and the development of GC. To explore the relationship between HBV SUPPORTING INFORMATION Additional supporting information may be found online in the Supporting Information section. How to cite this article: Cui H, Jin Y, Chen F, et al. Clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…As precancerosis to gastric cancer, gastric premalignant changes was found to be correlated with HBV infection 22 . Meta‐analyses also found the association between HBV infection and gastric cancer 43,44 . In our study, the seroprevalence of HBsAg was much higher in gastric cancer compared with matched controls ( p = 0.017).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As precancerosis to gastric cancer, gastric premalignant changes was found to be correlated with HBV infection 22 . Meta‐analyses also found the association between HBV infection and gastric cancer 43,44 . In our study, the seroprevalence of HBsAg was much higher in gastric cancer compared with matched controls ( p = 0.017).…”
Section: Discussionsupporting
confidence: 68%
“…Chronic inflammation triggered by HBV caused immunosuppression which might play a role in gastric carcinogenesis. Cui et al found cellular atypia and lymphocytes’ infiltration induced by HBX in gastric epithelial cells 44 . As the oncogenic protein, HBX might also involve in the development of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As a causative pathogen for hepatocellular carcinoma, HBV infection was shown to be associated with the risk of GC in some sporadic studies ( 9 , 57 ). One meta‐analysis that included 3 case–control studies and 5 cohort studies also found that HBV infection is associated with a higher risk for GC (OR = 1.23, 95% CI 1.10–1.37) ( 58 ). As shown in this study, HBV DNA was investigated directly in gastric mucosa tissue by polymerase chain reaction method only in 2 studies with the low positive rate (0%–3.2% in GC), which was consistent with a previous study ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and epidemiological evidence supports the contribution of various viruses, including EBV, hepatitis virus, cytomegalovirus with gastritis and gastric cancer induced by H. pylori [67], and several studies have shown that gastric microbiota can regulate H. pylori infection and vice versa; this bacterium can modify the gastric microbiota composition [68][69][70]. On the other hand, the microbiota composition in several body niches exerts direct or indirect effects on virus infections, including EBV and human papilloma virus [71].…”
Section: Discussionmentioning
confidence: 98%